Suitability of Selected Diagnostic Factors for Assessing the Technical Condition of the Working Systems of Bucket Elevators - Piotr Sokolski (Energies)
This article proposes a method for diagnosing the main systems of bucket elevators in order to ensure their reliable operation. This method employs diagnostic indices of vibration velocity and vibration acceleration, which were deemed useful based on tests performed on four bucket elevators operating in a research laboratory and in a power plant. This article also analyzes other indicators, such as the coefficient of variation, skewness, kurtosis, crest factor, and quantile peak factor, and demonstrates the usefulness of kurtosis for diagnostic evaluation. Additionally, it proposes using the quantile peak factor as an alternative to the crest factor. This study estimates the statistical distributions of diagnostic signals and presents the results in the form of histograms. This is followed by the detection of outliers in all measurement series. Based on the results of the performed tests and their analysis, recommendations are made for diagnosing bucket elevators.